Prevalence of dental caries, the effect of sugar intake and tooth brushing practices in children aged 5-11 years in Bangalore North - Deepak Viswanath; Nimmy Sabu (Wolters Kluwer Medknow Publications, 2014)
Background: Dental caries is the most prevalent disease worldwide, and is caused by a complex interaction of tooth susceptibility, nutrition, and oral environment. The relationship between sugar intake, which includes the type of sugar being consumed, and the prevalence of dental caries has long been a subject of dispute. Aim: Aim of this study was to determine the effect of sugar types, frequency of sugar intake and oral hygiene practices on dental caries among school children of both genders aged 5-11 years from Bangalore North. Methods: A specially designed questionnaire was used to collect information regarding type of sugar intake, frequency of sugar consumption and the regularity of tooth brushing among children. All the children were examined clinically to assess their dmft/DMFT score. The obtained data was analyzed using ANOVA and Student's t-test. Results: The mean ± SD values of dmft and DMFT in children taking candies were 3.03 ± 2.66 and 0.33 ± 0.64 respectively. The mean ± SD value of dmft and DMFT in children with tooth brushing once daily was 2.55 ± 2.51 and 0.28 ± 0.77 respectively, while that in children with tooth brushing twice daily was 1.67 ± 1.98 and 0.21 ± 0.66 respectively. Hard candies were found to be more risky in causing dental caries than soft drinks or ice cream. Conclusion: From the results of our study, there was a direct association between the frequency of sugar consumption and dental caries and tooth brushing practice can minimize the severity and prevalence of dental caries.